NAME Readymade - Forum Stadtpark Graz; Moderna Galerija Ljubljana - Museum of Modern Art (Ljubljana : Moderna Galerija Ljubljana - Museum of Modern Art, 2008)
Jansa, Janez; Lukan, Blaz; Jones, Amelia; Badovinac, Zdenka; Suvakovic, Misko; Soussloff, Catherine M.; Kavacic, Tadej; Milohnic, Aldo; Caronia, Antonio; Kreft, Lev; Krecic, Jela
Engels
Exhibition. NAME Readymade. Graz. Forum Stadtpark Graz. Moderna Galerija Ljubljana - Museum of Modern Art. 2008-10-04. 2008-10-25
boek